2021
DOI: 10.3390/molecules26113466
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Biological Evaluation and Silico Prediction of Novel Sinomenine Derivatives

Abstract: Sinomenine is a morphinan alkaloid with a variety of biological activities. Its derivatives have shown significant cytotoxic activity against different cancer cell lines in many studies. In this study, two series of sinomenine derivatives were designed and synthesized by modifying the active positions C1 and C4 on the A ring of sinomenine. Twenty-three compounds were synthesized and characterized by spectroscopy (IR, 1H-NMR, 13C-NMR, and HRMS). They were further evaluated for their cytotoxic activity against f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In 2021, researchers reported that the highly active compound 6d ( 8 ) exhibited notable cytotoxicity through the PI3K/AKT and MAPK signaling pathways, with IC 50 values ranging from 3.46 µM to 11.51 µM against various cancer cell lines (MCF-7, HeLa, HepG2, SW480, and A549). However, compound 6d demonstrated less selectivity towards the normal cell line Hek293, with an IC 50 of 3.46 µM [ 66 ]. G.H.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…In 2021, researchers reported that the highly active compound 6d ( 8 ) exhibited notable cytotoxicity through the PI3K/AKT and MAPK signaling pathways, with IC 50 values ranging from 3.46 µM to 11.51 µM against various cancer cell lines (MCF-7, HeLa, HepG2, SW480, and A549). However, compound 6d demonstrated less selectivity towards the normal cell line Hek293, with an IC 50 of 3.46 µM [ 66 ]. G.H.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Then HeLa cells were placed in 96-well plates with a total of 6500 cells per well. [23][24][25] The treated HeLa cells were incubated with various concentrations of probe HAM (ranging from 0 to 100 mM) for 24 h. Following incubation, CCK-8 solution was supplemented and HeLa cells were further incubated for 4 h. The cell viability was determined according to the optical density of the experimental group. HeLa cells were rst incubated with probe HAM in 96-well plates for 24 h. The selected HeLa cells were incubated with probe HAM (10 mM) for 30 min.…”
Section: Cytotoxicity Study and Cell Imagingmentioning
confidence: 99%
“…Moreover, many studies have showed that structural modification is effective to improve bioactivity and to reduce side effect. Several structural modifications of SIN have been attempted in many research groups with great success [16–18] . Figure 1 summarizes the structure and important modification sites of SIN.…”
Section: Introductionmentioning
confidence: 99%
“…Several structural modifications of SIN have been attempted in many research groups with great success. [16][17][18] Figure 1 summarizes the structure and important modification sites of SIN. Among them, structural modification on C1 and C4 of SIN had been found particularly suitable for antitumor activity.…”
Section: Introductionmentioning
confidence: 99%